Hubungan Mutu Pelayanan Kesehatan dengan Kepuasan Pasien Poli Umum di Puskesmas Kecamatan Menteng - Muhamad Al Imran Rangga Putra; Puteri Fannya; Deasy Rosmala Dewi; Muniroh Muniroh (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Quality health services are healthcare services that are patient-centered, caring, and focused on meeting the needs, expectations, and values of patients. These services serve as benchmarks for healthcare delivery and must fulfill specific requirements to ensure patient satisfaction. Patient satisfaction refers to the perceived quality of healthcare services as experienced by the patient or their closest family members. Satisfaction is achieved when optimal outcomes are obtained while considering the capabilities and circumstances of the patient or family.